Professional certification in ecological restoration: improving the practice and the profession. Issue 1 (January 2017) - Nelson, Cara R.; Bowers, Keith; Lyndall, Jennifer L.; Munro, John; Stanley, John T.
Abstract : Given increasing investments in ecological restoration around the globe, there is a need to develop standards of practice to improve professional training and encourage the highest quality of performance possible. Although professional certification is a mechanism for promoting and improving the profession, until now certification has not been available to individuals who practice ecological restoration. The Society for Ecological Restoration (SER) is launching a professional certification program in early 2017. The program requires professional experience, a knowledge base in five broad subject areas, understanding of the foundations of the profession, and adherence to a code of ethics. The SER certification program will certify both practitioners (Certified Ecological Restoration Practitioners [CERPs]) and practitioners‐in‐training (Certified Ecological Restoration Practitioners‐in‐training [CERPITs]).